The Effect of Ethanol Extract of Starfruit Leaves (Averrhoa Bilimbi L.) on Total Cholesterol Levels in White Wistar Male Rats Induced by High-Fat Feed - Lestari Silitonga; Erida Novrian; Nerly Juli Ranita Simanjuntak (Jurnal Multidisiplin Sahombu, 2026)
Indonesia has high biodiversity and great potential as a source of traditional medicine. Lipid metabolism disorders, particularly increased total cholesterol levels, are a major risk factor for cardiovascular disease, the prevalence of which continues to increase due to high-fat consumption patterns and lifestyle changes. The starfruit plant (Averrhoa bilimbi L.) is known to contain secondary metabolites such as flavonoids, saponins, tannins, and alkaloids that have the potential to play a role in lowering total cholesterol levels. This study aims to determine the effect of administering ethanol extract of starfruit leaves (Averrhoa bilimbi L.) on total cholesterol levels in male Wistar rats induced by a high-fat diet. This study is an experimental study with a post-test control group design. A total of 30 male Wistar rats were divided into six groups, namely normal control (KN), negative control (K-), positive control (K+), and three treatment groups given starfruit leaf extract at a dose of 120 mg/KgBW (P1), 240 mg/KgBW (P2), and 480 mg/KgBW (P3). The rats were induced with a high-fat diet for 14 days, then given treatment for 14 days. Total cholesterol levels were examined on days 8, 22, and 35. Data were analyzed using the Shapiro-Wilk test, Levene's test, One-Way ANOVA, and Games-Howell follow-up test. The results showed that high-fat feed induction successfully increased total cholesterol levels in the negative control group. Administration of starfruit leaf extract at all doses significantly reduced total cholesterol levels compared to the negative control group (p<0.05). The 240 mg/kgBW dose (P2) showed the most effective reduction in total cholesterol levels with a mean value of 104.80 ± 3.11 mg/dL, comparable to the positive control group (simvastatin). Ethanol extract of starfruit (Averrhoa bilimbi L.) leaves effectively reduced total cholesterol levels in male Wistar rats fed a high-fat diet, with the most effective dose being 240 mg/kgBW. This extract has the potential to be developed as an alternative to traditional antihyperlipidemic drugs.